2019
DOI: 10.1002/cam4.2799
|View full text |Cite
|
Sign up to set email alerts
|

Using circulating tumor DNA as a novel biomarker to screen and diagnose hepatocellular carcinoma: A systematic review and meta‐analysis

Abstract: Purpose A meta‐analysis was formulated to appraise the diagnostic accuracy of circulating tumor DNA (ctDNA) in hepatocellular carcinoma (HCC). Materials and Methods We enrolled all relevant studies published until September 2019. Four primary subgroups were investigated: the subgroup of quantitative or qualitative analysis of ctDNA, the subgroup of Ras association domain family 1 isoform A (RASSF1A) methylation in ctDNA and the subgroup of the combined alpha‐fetoprotein (AFP) and ctDNA assay. We analyzed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Kaplan-Meier plots with log-rank tests were applied to evaluate the association between overall survival (OS) of patients with ccRCC and PKMYT1 expression. A receiver operating characteristic curve (ROC) with areas under the curve (AUC) was formulated to assess the diagnostic efficiency of PKMYT1 in ccRCC [ 34 , 35 ]. Cox regression analysis was used to calculate the hazard ratio (HR) with 95% confidence interval (CI) to estimate the prognostic effect of PKMYT1 in ccRCC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan-Meier plots with log-rank tests were applied to evaluate the association between overall survival (OS) of patients with ccRCC and PKMYT1 expression. A receiver operating characteristic curve (ROC) with areas under the curve (AUC) was formulated to assess the diagnostic efficiency of PKMYT1 in ccRCC [ 34 , 35 ]. Cox regression analysis was used to calculate the hazard ratio (HR) with 95% confidence interval (CI) to estimate the prognostic effect of PKMYT1 in ccRCC.…”
Section: Methodsmentioning
confidence: 99%
“…A nomogram was developed with the “rms” R package to estimate the probability of 3-, 5-, and 10-year OS in patients with ccRCC. A concordance index (C-index) and calibration plot were applied to evaluate the nomogram discrimination and the consistence between nomogram prediction and practical observation, respectively [ 34 , 35 ]. The time-dependent ROC curves were applied to evaluate the predictive capability of the nomogram, PKMYT1 expression level, and additional clinicopathologic variables for 3-, 5-, and 10-year OS.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the AUC of AFP (0.960) in our study was much higher than the previously reported range (AUC: 0.64-0.77). [18][19][20] This phenomenon could be due to the fact that most of our patients were at the advanced stage of HCC, and therefore, presented significantly elevated levels of AFP. The ROC curve for NONHSAT053785 showed a promising AUC value of 0.801, with a sensitivity of 73.2% and a specificity of 75.4%.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, a staggering proportion (57%) of LUAD cases initially diagnosed with metastatic neoplasm achieves a 5‐year survival rate of merely 5% 6 . Conversely, low‐dose computerized tomography (CT) is conducive to the rapid screening of early‐stage LUAD 7,8 . Those with localized tumor exhibit a relatively desirable 5‐year survival rate of up to 83% (TNM stage IA) and 71% (TNM stage IB) 9 .…”
Section: Introductionmentioning
confidence: 99%